A Facile Route to Cotton-Like BiOCl Nanomaterial with Enhanced Dye-Sensitized Visible Light Photocatalytic Efficiency - 赵梅 董立峰 李成栋 于立岩 李平 (Chinese physics letters, 2015)
A facile route is developed to fabricate BiOCI porous cotton-like nanostructure by using Bi203 and hydrochlo- ric acid as raw materials. The BiOCI nanomaterial is actually hierarchically structured by numerous ultrathin nanosheets. The nanosheets are around 50-500 nm in lateral size and 2-12 nm in thickness. High-resolution trans- mission electron microscopy and selected-area electron diffraction analyses indicate that single-crystalline BiOCl nanosheets have the predominant growth direction along [110], the bottom and top surfaces are {001} facets, and four lateral surfaces are {110} facets. The BiOCl nanosheets are dominantly enclosed by {001} facets. From the diffuse reflectance spectroscopy spectrum, the light absorption edge and band gap energy （Eg） are estimated to be 416 nm and 2.98eV, respectively. The BiOCl photocatalyst possesses superior activity for methyl orange （MO） degradation under visible light irradiation and the photodegradation efficiency is up to 91.5%/180 min. The correlation between morphology and microstructure with enhanced MO-sensitized photodegradation performance under visible light is investigated.